2011
DOI: 10.1093/annonc/mdr006
|View full text |Cite
|
Sign up to set email alerts
|

Survival and human papillomavirus in oropharynx cancer in TAX 324: a subset analysis from an international phase III trial

Abstract: HPV+ OPC has a different biology compared with HPV- OPC; 5-year OS, PFS, and local-regional control are unprecedented. These results support the possibility of selectively reducing therapy and long-term morbidity in HPV+ OPC while preserving survival and approaching HPV- disease with more aggressive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
327
3
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(352 citation statements)
references
References 25 publications
15
327
3
7
Order By: Relevance
“…HR-HPV infection is an independent prognostic indicator (Weinberger et al, 2006;Kumar et al, 2007;Fakhry et al, 2008;Gillison et al, 2000;Hafkamp Kuo et al, 2008;Worden et al, 2008;Lill et al, 2011;Posner et al, 2011). Kuo and colleagues reported that the 5-year overall survival rate of patients with HR-HPV positive OSCC was 89%, which was significantly higher than HR-HPV negative patients (61%, p=0.001) (Kuo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…HR-HPV infection is an independent prognostic indicator (Weinberger et al, 2006;Kumar et al, 2007;Fakhry et al, 2008;Gillison et al, 2000;Hafkamp Kuo et al, 2008;Worden et al, 2008;Lill et al, 2011;Posner et al, 2011). Kuo and colleagues reported that the 5-year overall survival rate of patients with HR-HPV positive OSCC was 89%, which was significantly higher than HR-HPV negative patients (61%, p=0.001) (Kuo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that HPV-attributable oropharyngeal squamous cell carcinomas (OPSCCs) have a unique biology and also have improved treatment responses and patient outcomes. 2,3 Knowledge of HPV status does provide prognostic information, and more importantly, it may guide specific treatment decisions. At this moment, clinical trials are being conducted to investigate de-escalation of therapy for patients with an HPV-positive OPSCC.…”
mentioning
confidence: 99%
“…While the favorable prognostic significance of HPV +/p 16 + expression is well established in OPSCC, the prognostic significance of HPV and/or p 16 expression in non-OPSCC is not clearly delineated [21], [20], [29]. Our study cohort consisted mainly of SCC of the larynx, hypopharynx, and oral cavity (57.1%, 16.7%, and 14.3% respectively) while only 4.8% (2/42 patients) had OPSCC.…”
Section: Discussionmentioning
confidence: 93%